MEDIASI FINANCIAL LITERACY DALAM HUBUNGAN FINANCIAL TECHNOLOGY PAYMENT DAN FINANCIAL ATTITUDE TERHADAP CHANGES IN PEOPLE'S FINANCIAL BEHAVIOR DALAM PERSPEKTIF BISNIS ISLAM - Habibah, Umi; Ekawati, Evi; Susanto, Is (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: The development of digital technology, especially fintech payments, has facilitated transactions and made financial management more digital and flexible. This study aims to analyse the role of financial literacy mediation in the relationship between financial technology payment and financial attitudes towards changes in people's economic behaviour, considering the Islamic business perspective.Methods: Using a quantitative approach with the SEM-PLS analysis technique, 100 respondents were surveyed through a Google form using a purposive sampling technique. The results show that fintech payment and financial attitude intentionally increase financial literacy, which then has a positive effect on changes in people's economic behaviour.Results: This study found that financial literacy partially mediates the relationship between fintech payments and financial attitudes, influencing changes in people's financial behaviour. Although the direct influence of fintech payments and financial attitudes on changes in financial behaviour has proven to be more dominant, the mediating role of financial literacy remains significant, which shows that increasing financial literacy encourages wiser and more responsible financial behaviour. From an Islamic perspective, financial literacy acts as a mediator, connecting fintech payments and financial attitudes to change people's financial behaviour by applying sharia principles such as honesty, justice, and the prohibition of usury. Islam's emphasis on business ethics, including transparency and price fairness, is reflected in e-commerce regulations to create a fair and trustworthy digital ecosystem. Keywords: Financial Literacy, Fintech Payment, Financial Attitude, Financial Behaviour, Bisnis Islam.